A Study on the Performance of Micro, Small and Medium Enterprises (Msmes) and Role of HRM in SME’s in India - Gayathri, N. Lakshmi; Jayanthi, Prasad Babu (The journal of contemporary issues in business and government, 2019)
The MSME sector is considered to be the engine of growth for an economy. The estimated contribution of Micro, Small and Medium Enterprises (MSME) sector, including service segment, to the country’s GDP during 201213 was 37.54 per cent; while the total employment in the sector is 805.24 Lakh. The contribution of the sector to India’s total export for the year 2014- 15 was 44.70 per cent. Also the problems of poverty and inequality are deep- rooted, especially in developing countries like India. To address these problems, we need a system of ‘Inclusive Growth’. Growth cannot be inclusive unless and until the fruits of the growth is percolated to the bottom of pyramid. Specifically in a developing nation like India where inequality in distribution of wealth and income is significantly high, sustained increase in ii. iii. A small enterprise is an enterprise where the investment in plant and machinery is more than Rs. 25 lakh but does not exceed Rs. 5 crore; and A medium enterprise is an enterprise where the investment in plant and machinery is more than Rs.5 crore but does not exceed Rs.10 crore. In case of the above enterprises, investment in plant and machinery is the original cost excluding land and building and the items specified by the Ministry of Small Scale Industries vide its notification No.S.O.1722 (E) dated October 5, 2006. per capita income cannot be translated automatically to sustained increase in standard of living. In order to alleviate the curse of poverty, inequity, unemployment and underemployment, adequate employment opportunities should be created for the poor mass which will facilitate them to meet their subsistence level of consumption demand. This paper attempts to assess the performance of MSME sector in India.